2021
DOI: 10.1093/ehjcr/ytaa553
|View full text |Cite
|
Sign up to set email alerts
|

ST-segment elevation in patients presenting with COVID-19: case series

Abstract: Background  The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the pathogen responsible for the now pandemic disease, coronavirus disease (COVID-19). A number of reports have emerged suggesting these patients may present with signs and symptoms consistent with ST-segment elevation myocardial infarction without coronary artery occlusion. Case summary  We report an international case series of patients with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
1
11
0
2
Order By: Relevance
“…Overall, the prognosis was poor across groups with 30% in-hospital mortality rate. In accordance with the above review, M. Saririan et al [61] reported a case series where three confirmed COVID-19 positive patients with STEMI presented with negative angiographic evidence of atherothrombotic type I MI thereby suggestive of type II MI. All the three patients had patent coronary arteries on coronary angiography.…”
Section: Covid-19 With Stemi With and Without Obstructive Cadsupporting
confidence: 54%
“…Overall, the prognosis was poor across groups with 30% in-hospital mortality rate. In accordance with the above review, M. Saririan et al [61] reported a case series where three confirmed COVID-19 positive patients with STEMI presented with negative angiographic evidence of atherothrombotic type I MI thereby suggestive of type II MI. All the three patients had patent coronary arteries on coronary angiography.…”
Section: Covid-19 With Stemi With and Without Obstructive Cadsupporting
confidence: 54%
“…[ 36 ]; [ 37 ]; [ 38 ]; [ 39 ]; [ 40 ]; [ 41 ]; [ 42 ]; [ 43 ]; [ 44 ]; [ 45 ]; [ 46 ]; [ 47 ]; [ 48 ].…”
Section: Uncited Referencesunclassified
“…Several case studies have reported the association between COVID-19 infection and AMI [8][9][10]. Saririan et al published a case series of 3 patients with COVID-19 infection presenting with STEMI [9].They reported the incidence of myocardial injury in hospitalized patients with COVID-19 to range from 23% to 27.8%.…”
Section: Discussionmentioning
confidence: 99%